Performance evaluation of different types of cutting fluid in the machining of aisi 01 hardened steel using pulsed jet minimal quantity lubrication system - Hamdan, A.; Fadzil, M.; Abou-El-Hossein, K.A.; Abd Shukor, Mohd Hamdi (AUN/SEED-Net, 2011)
This paper presents the performance evaluation of three different cutting fluids used in a minimal quantity lubrication (MQL) system. The MQL system, developed in-house at the University of Malaya, was capable of delivering high velocity cutting fluid in narrow pulsed jet forms at a rate of 2 ml/min and a pressure of 20 MPa. The three cutting fluids chosen were neat oil, soluble oil and semi-synthetic cutting fluids. The experiments were designed to evaluate the performance of the fluids at various cutting velocities of 20,40 and 60 m/min and feed rates of 0.05,0.06 and 0.07 mm/tooth. The results were measured in terms of the average surface roughness of the machined workpiece, the cutting forces and the maximum flank wear. In addition, the resultant chip formations were also observed. Analysis of the results has shown that in general, neat oil had performed the best in low cutting velocities and feed rates. On the other hand, soluble oil gave the lowest cutting forces and flank wears at high cutting velocities and feed rated as compared to neat oil and synthetic cutting fluid. It was observed that performance of soluble oil does not drastically change with variation to the cutting velocities and feed rates. Thus, the choice of soluble oil would be most appropriate for general machining usage. With suitable machining parameter selection, water-mixed cutting fluids (soluble oil and semi synthetics) performed comparatively well to deliver low surface roughness results. Therefore, this can be an economical choice for use in industrial production processes.